Negative impacts of capital structure on efficiency of joint stock companies listed on Vietnamese Stock market - Do, Phuong Huyen at al. (Tạp chí Công thương, 2020)
The research investigates the relationship between capital structure and firms operational efficiency of joint companies listed on Vietnamese stock market. The main hypothesis represents the negative effects of capital structure on the operational efficiency. By using samples of 150 companies over 2016-2017 and Pooled-OLS model, thr research affirmed that there is a negative relationship between capital structure and operational efficiency. Other independent variables including size, asset structure, total asset growth and liquidity are significant determinants of how firms oerform.